Stress and your health from vulnerability to resilience - Anisman, Hymie (Southern Gate, Chichester, West Sussex, UK Wiley Blackwell, 2015)
"Stress and Your Health: From Vulnerability to Resilience presents an evidence-based evaluation of the various effects of stress, along with methods to alleviate distress and stress-related illnesses. Examines myriad stressor effects and proven ways to alleviate stress in our lives Covers a wide range of stressor-related topics including therapeutic strategies to deal with stress and factors that hinder treatment of stress Makes difficult biochemical and immunological concepts accessible to a non-specialist audience Addresses many of the factors that cause individuals to be more vulnerable to the impact of stressors and at increased risk for pathology "--Provided by publisher.
"Covers a wide range of stressor-related topics including therapeutic strategies to deal with stress and factors that hinder treatment of stress."--Provided by publisher.
Includes bibliographical references (pages 269-271) and index.
Keywords: Stress (Psychology); Health; Psychophysiology